A Study on Sustainability of Contemporary Cropping Systems in Bam - Zarei, Fatemeh; Baniasadi , Somaye (Advances in Social Sciences Research Journal, 2020)
The study was conducted in Bam in 2019 to develop an index to quantify sustainability of cropping systems in the region. The studied cropping systems included single-cropping systems (palm trees) and multi-cropping systems (citrus, palm trees and alfalfa). The studied indices included economic, social, agricultural indices, as well as, personal features, market access, features of communication, education-extension activities, sustainable agricultural knowledge, attitude towards sustainable agriculture, and obstacles facing sustainable agriculture. The results indicated that the amount of sustainability index was lower than the mean value in 0.56% of the farms and this index was higher than the mean value in 0.44% of the others. Comparison of the mean value of sustainability indices in the studied cropping systems indicated that the mean indices of the type of cropping system, attitude towards sustainable agriculture and extension training activities in multi-cropping systems were more than single crops. The mean indices in social participation and the obstacles facing sustainable agriculture in single cropping systems was more than the multi-cropping ones. Some indices including social participation, sustainable agricultural knowledge and education-extension activities in multivariate regression model remained in the final model as variables that had the largest contribution in the rate of change in the dependent variable (sustainability) and explained = 60% of the changes in the dependent variable. The study showed that the sustainability of multi-cropping systems was more than the single-cropping ones.